2018
DOI: 10.4000/gc.7118
|View full text |Cite
|
Sign up to set email alerts
|

Géographie des fantômes

Abstract: Nous tenons à remercier chaleureusement Serge Weber pour sa relecture critique et stimulante de cette présentation. « La guerre est finie bêtement, sans qu'il ne se passe rien, sans un regret, sans un élan. Elle n'a rien laissé à penser. Tous les cadavres sans sépultures vont remonter, forcément. »

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Because it is stuck in this liminal stage in which apartheid wrongs have not yet been righted, post-apartheid is the space-time of ghosts. Again, this is not specific to South Africa: Marie Bonte has shown that in a post-conflict situation that might just as well be pre-conflict, Beirut teems with them (Barthe-Deloizy et al, 2018; Bonte, 2017). They might be haunting memories that persist and which one has to confront unexpectedly, or the phantoms of people forcibly displaced, kidnapped, murdered, and massacred.…”
Section: Post-apartheid As Entangled Space-timementioning
confidence: 99%
“…Because it is stuck in this liminal stage in which apartheid wrongs have not yet been righted, post-apartheid is the space-time of ghosts. Again, this is not specific to South Africa: Marie Bonte has shown that in a post-conflict situation that might just as well be pre-conflict, Beirut teems with them (Barthe-Deloizy et al, 2018; Bonte, 2017). They might be haunting memories that persist and which one has to confront unexpectedly, or the phantoms of people forcibly displaced, kidnapped, murdered, and massacred.…”
Section: Post-apartheid As Entangled Space-timementioning
confidence: 99%